Development of colloidal semiconductor nanocrystals : synthesis, properties and their outlook for light emitting diodes (LEDs) - Kaur, Manpreet (2020)
In recent years, the optimum properties of colloidal nanocrystals have widespread its usage in electronics and optoelectronics applications. The advancement in synthesis enables control over the size, shape, crystal structure and composition of nanocrystals. It facilitates control over optical and physical properties of colloidal nanocrystals. They have tremendous potential to be used in different applications. This review focuses on recent progress in the study of colloidal semiconductor nanocrystals. Here, we review the advances in the synthesis techniques, optical properties, surface modification with ligand treatment and doping in colloidal semiconductor nanocrystals. This enables their use in various applications such as light emitting diodes, lasers, solar cells, biomedical labelling and gas sensors. Literature studies reveal that the incorporation of any impurity element or defect into semiconductor affects its optical properties as well other physical properties. Binary semiconductor nanocrystals from different groups have high degree of ionicity making them suitable for various applications. With the advancement in technology, ternary semiconductor nanocrystals have replaced the binary nanocrystals as they possess tunable emission in the visible region of spectrum. In this review, we have summarized different ternary semiconductor nanocrystals which have been applied in light emitting diodes, biosensor, imaging, solar cell and drug delivery.